Cognitive impairments in first-episode drug-naive and chronic medicated schizophrenia: MATRICS consensus cognitive battery in a Chinese Han population. (30th April 2016) - Wu, Jing Qin; Chen, Da Chun; Tan, Yun Long; Xiu, Mei Hong; De Yang, Fu; Soares, Jair C.; Zhang, Xiang Yang
Abstract: Cognitive deficits are a core feature of schizophrenia and we examined the cognitive profile of first-episode and chronic schizophrenia in a Chinese Han population using the MATRICS Consensus Cognitive Battery (MCCB). We recruited 79 first-episode drug-naïve (FEDN) schizophrenia, 132 chronic medicated schizophrenia inpatients and 124 healthy controls. We assessed patient psychopathology using the Positive and Negative Syndrome Scale (PANSS). MCCB total score (p<0.01) and index scores of category fluency, trail making A, digital sequence, Hopkins Verbal Learning Test (HVLT), mazes, and Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) were significantly higher in FEDN than in chronic patients (all p<0.05). FEDN exhibited relative weakness in continuous performance, whereas chronic patients exhibited relative weakness in mazes. Multiple regression analysis confirmed that in FEDN and chronic patients, total score and negative symptom of PANSS were independent contributors to MCCB total score, respectively. Our results not only demonstrate the applicability of the MCCB as a sensitive measure of cognitive impairment for schizophrenia patients in a Chinese Han population, but also suggest that the compromised cognition is present in the early stage of schizophrenia, some of which could be more severe in the chronic stage of illness. Highlights: MCCB was examined in 79 first-episode, 132 chronic schizophrenia and 124 controls. Both first-episode and chronic patients showed widespread cognitive impairments MCCB total and 6 index scores were higher in first-episode than in chronic patients. Cognitive deficits are present in the early stage of schizophrenia, and are worse in its chronic stage.